Tooth as a Bone Graft Material: A Narrative Review - Obulareddy, Vishnu Teja; Porwal, Amit; Noor, Toufiq; Catalano, Francesco; Minervini, Giuseppe; D'Amico, Cesare; Mancini, Maura; Gorassini, Francesca; Fiorillo, Luca; Cervino, Gabriele (European Journal of General Dentistry, 2023)
To treat osseous defects, a range of bone grafts and their replacements have been accessible, but appropriate reconstruction by any bony defect persists as a therapeutic hurdle. Based on peer-reviewed literature, the current narrative review analyzes significant outcomes in patients treated with bone grafts and bone graft substitutes for surgical therapy of osseous defects. Despite autograft, xenograft, and alloplastic bone graft substitutes being employed in several periodontic procedures, they all have their restrictions. Autogenous tooth bone graft is functional in clinics due to different available forms, which can be availed for other clinical challenges. Moreover, genetic uniformity fosters efficient bone regeneration by allowing osteoinduction and osteoconduction and reducing foreign body reactions.
Keywords: alloplastic; bone graft; oral surgery; regenerative surgery; tooth